2023
DOI: 10.1007/s12633-022-02286-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Olive Stones and Corncobs Crystalline Silica Nanoparticles (SiO2, NPs) Treatments on Potato Tuber Moths (Phthorimaea Operculella)

Abstract: Morphological and microstructural properties of silica (SiO 2 ) are essential factors that need to be considered during the experimental applications. In this report, SiO 2 nanoparticles (NPs) have been prepared at different concentrations from SiO 2 powder derived from olive stones and corncobs by an alkali leaching extraction method. Thermal treatment has been used to modify the morphological and microstructural properties of the extracted SiO 2 . X-ray diffraction (XRD) shows that the extracted amorphous Si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, their efficacy as pesticides may vary depending on their origin and composition. For example, the efficacy of a compound derived from crystalline silica samples was found to be lower in suppressing potato tuber moth when compared to that derived from amorphous silica powders [ 171 ]. Studies have demonstrated that this type of NP can exert toxic effects on non-target organisms.…”
Section: Nano-agrochemicals (Nacs)mentioning
confidence: 99%
“…However, their efficacy as pesticides may vary depending on their origin and composition. For example, the efficacy of a compound derived from crystalline silica samples was found to be lower in suppressing potato tuber moth when compared to that derived from amorphous silica powders [ 171 ]. Studies have demonstrated that this type of NP can exert toxic effects on non-target organisms.…”
Section: Nano-agrochemicals (Nacs)mentioning
confidence: 99%
“…30 and 8.14 µg/L to adults that emerged from pupae aged (1-2) and (6-8) days respectively. The use of silicon dioxide nanoparticles for the control of this type of pests is also possible (Idris et al, 2023). On the other hand, Kirisik et al (2023) studied the trapping efficiencies of a newly designed light trap and a delta pheromone trap were comparatively evaluated in mass trapping of adult PTMs on stored potatoes during the storage period from October to December in 2019 and 2020 in Antalya province in Turkey; the results indicated that significantly more moths were captured per trap in the light trap rooms than in the pheromone trap plots so the tuber damage rate was relative to the moth capture.…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of the species cause damage by mining leaf tissues and tunneling into tubers, leading to surface deformities and rot. Without refrigeration, crop losses can reach 50-100% [6]. Presently, chemical pesticides Life 2023, 13, 2174 2 of 14 are the primary means of control, but their effectiveness is limited due to the pest's leafmining and tunneling behavior.…”
Section: Introductionmentioning
confidence: 99%